2008
DOI: 10.1111/j.1365-2222.2008.02977.x
|View full text |Cite
|
Sign up to set email alerts
|

Asp–Tyr–Leu–Lys tetrapeptide inhibits airway inflammation in toluene‐2,4‐diisocyanate‐induced asthma mice

Abstract: Local administration of DYLK effectively inhibits the airway inflammation and airway remodelling of TDI-sensitized/challenged mice via down-regulation of VEGF. These findings suggest that anti-angiogenic peptide therapies, such as local administration of DYLK, are an effective strategy for the treatment of remodelling in asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…1). 13,19 As a control group, sham mice were sensitized and challenged with only a mixture of ethyl acetate/olive oil. SD rat BMDMSCs (1×10 5 cells) were transferred to the TDI-induced asthma mice intravenously via tail-vein injection 1 day before the TDI challenge.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). 13,19 As a control group, sham mice were sensitized and challenged with only a mixture of ethyl acetate/olive oil. SD rat BMDMSCs (1×10 5 cells) were transferred to the TDI-induced asthma mice intravenously via tail-vein injection 1 day before the TDI challenge.…”
Section: Methodsmentioning
confidence: 99%
“…For histological examination, 4-µm sections of embedded tissue were cut on a rotary microtome, placed on glass slides, deparaffinized, and stained sequentially with hematoxylin and eosin (H&E) and periodic acid-Schiff (PAS). The severity of peribronchial inflammation was graded semiquantitatively as previously described: 0, normal; 1, a few cells; 2, a ring of inflammatory cells one cell deep; 3, a ring of inflammatory cells more than four cells deep 19,23. We counted PAS-positive epithelial cells and all epithelial cells using software (Nikon DXM 1200; Nikon, Tokyo, Japan; and Image-Pro Plus 4.01; Media Cybernetics, Bethesda, MD, USA).…”
Section: Methodsmentioning
confidence: 99%
“…This suggested that VEGF regulation may be therapeutic in asthma and other Th2‐related disorders. It was also suggested that VEGF may be one of the major determinants of TDI‐induced asthma in murine models of TDI‐induced asthma, and that inhibition of VEGF may be a good therapeutic strategy [11, 12]. Furthermore, numerous reports have shown increases in lung vasculature in asthmatics, and a strong correlation between the degree of vascular abnormalities and asthma severity [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…Application of 0.5% IgE pentapeptide intranasal solution appears to be safe and effective in the treatment of allergic rhinitis. (Prenner BM., 1987) Another finding suggests that tetrapeptide DYLK, when administered locally, can effectively inhibit the airway inflammation and airway remodeling of TDI-sensitized/challenged mice via down-regulation of VEGF, implicating a role in the treatment of allergic reaction in asthma (Ahn MH et al, 2008) The skin is a unique immunological organ that integrates the external environment with the systemic immune response. To perform sensitization testing is an efficient way to predict allergens.…”
Section: Review Of Literaturementioning
confidence: 99%